Role of magnetic resonance imaging on fingers in diagnosis of post-traumatic tendon and ligament injuries - Mohammed Abd El Aziz Mssaaly (SpringerOpen, 2021)
Abstract Background Magnetic resonance (MR) imaging is a powerful method for evaluating acute and chronic lesions of the stabilizing articular elements (volar plate and collateral ligaments) of the fingers and thumbs, the condition of tendons, the presence of a tear, the number of affected tendons, the extent of tendon retraction, and the presence of associated lesions. This study was done to clarify the value of magnetic resonance imaging (MRI) in assessment of trauma-related injuries of the tendons and ligaments of the fingers and subsequently positively affect the surgical decisions in such cases. Results This study included 42 patients (33 males and 9 females) with a mean age of 35 years. All of them had history of trauma. Male affection was 78.5%, while females constituted only 21.5%, striking right-sided-hand affection (92.9%). The most affected finger was the thumb. The most common affected sites were extending from the metacarpophalangeal (MCP) till the proximal interphalangeal (PIP). The tendons were affected in 42.9%; meanwhile, ligamentous affection represented 57.2%. The flexor tendon tear represented by 28.6%%, while extensor tendon tear occurred in 14.3%. The study also showed that partial thickness tear is represented by 66.7%, while complete thickness tear occurred in about 33.3%. Bone marrow edema and post-traumatic tenosynovitis occurred in about 14% of cases. Conclusions Magnetic resonance imaging is an essential technique to obtain a correct pre-surgical diagnosis. It is of utmost importance to possess an in-depth knowledge of finger radiological anatomy in detail, as well as the appearance of the different pathologic entities on MRI. It provides a great assessment of the tendons and ligaments tear by whether partial or complete, any associated marrow edema or bony fragment avulsion and the extent of retraction in cases of complete tear.